Transabdominal Plane Block for Postoperative Pain Management: A Case Series - Iwan Setiawan Makmur; Nur Surya Wirawan (HM Publisher, 2022)
Introduction: Post-surgery pain is the most common problem found in patients in the treatment room, which can provide patients with emotional experiences that have an impact on the recovery process. This study aims to present a case series of post-operative pain management with transversus abdominis plane (TAP) block and its outcomes. Case presentation: This study was conducted at the Polewali General Hospital, West Sulawesi, Indonesia. There were three patients who participated in this study, namely elective Caesarean section (C-section), emergency C-section and herniorrhaphy. The first patient had adequate analgesia, although the onset of the anesthetic drug worked perfectly two hours after the injection. In the second patient, the patient did not complain of severe pain the day after the transversus abdominis block action. The third patient made an excellent recovery. This patient was not given opioids for post-operative analgesia, only using Dexketoprofen every eight hours intravenously. The next day the patient could be scheduled for outpatient treatment. Conclusion: TAP block is one of the post-operative analgesia techniques that have good analgesia quality, especially when combined with other analgesic drugs in multimodal analgesia techniques.